Production of thermostable T1 lipase using agro-industrial waste medium formulation / Hisham Mohd Nooh ... [et al.] - Mohd Nooh, Hisham; Masomian, Malihe; Salleh, Abu Bakar; Mohamad, Rosfarizan; Mohamad Ali, Mohd Shukuri; Raja Abd. Rahman, Raja Noor Zaliha (2021)
Large-scale production of T1 lipase using conventional culture media is costly. To reduce the cost of production, an alternative growth medium using local resources has been developed. In this study, the growth of recombinant Escherichia coli and expression of T1 lipase were tested using different agro-industrial wastes as carbon and nitrogen sources by conventional method. Subsequently, by using central composite rotatable design (CCRD), a set of 30 experiments was generated to evaluate the effect of different parameters, including the amount of molasses (as carbon source), fish waste (as nitrogen source), NaCl, and inducer concentration on production of T1 lipase.